2017
DOI: 10.1186/s12876-017-0683-9
|View full text |Cite
|
Sign up to set email alerts
|

Faecal bacterial microbiota in patients with cirrhosis and the effect of lactulose administration

Abstract: BackgroundGut microbiota may be altered in patients with cirrhosis, and may further change after administration of lactulose. We studied the composition of gut microbiota in patients with cirrhosis and assessed the effect on it of lactulose administration.MethodsStool specimens were collected from 35 patients with cirrhosis (male 26; median [range] age: 42 [29–65] years) and 18 healthy controls (male 14; 44.5 [24–67] years); 21 patients provided another specimen after lactulose administration for 55 [42–77] da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…We were interested in the effect of lactulose on the cirrhotic microbiome, since available data are conflicting, showing no major alterations of the faecal microbiome between lactulose user and non-user, but withdrawal of lactulose leads to the loss of beneficial species. 16,50,51 In our cohort only 11% of the cirrhotic patients used lactulose. On univariate analysis we found that lactulose had a weak, but significant, effect on microbiome composition, which did not remain significant in multivariate analysis.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We were interested in the effect of lactulose on the cirrhotic microbiome, since available data are conflicting, showing no major alterations of the faecal microbiome between lactulose user and non-user, but withdrawal of lactulose leads to the loss of beneficial species. 16,50,51 In our cohort only 11% of the cirrhotic patients used lactulose. On univariate analysis we found that lactulose had a weak, but significant, effect on microbiome composition, which did not remain significant in multivariate analysis.…”
Section: Discussionmentioning
confidence: 76%
“…However, in our cohort, other drugs influenced microbiome composition to a lesser extent. We were interested in the effect of lactulose on the cirrhotic microbiome, since available data are conflicting, showing no major alterations of the faecal microbiome between lactulose user and non‐user, but withdrawal of lactulose leads to the loss of beneficial species . In our cohort only 11% of the cirrhotic patients used lactulose.…”
Section: Discussionmentioning
confidence: 99%
“…et al revealed that lactulose and probiotics could increase beneficial bacteria and reduce pathogenic bacteria in MHE. 15 Prior studies on lactulose and MHE are single-center experiences, 12,13 and a multicenter approach is lacking. In addition, the role of microbiota changes as mediators of lactulose responses need to be studied.…”
Section: Ziadamentioning
confidence: 99%
“…Lactulose, in studies primarily from India, has shown a beneficial impact on MHE reversal and on quality of life (QoL) . Further, Bajaj et al and Sarangi et al proved that NADs can beneficially affect microbiota composition. Thus, the therapeutic effect of lactulose for MHE was probably mediated by changing intestinal microbiota.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation